(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2016)
BIG DATA Big data is a collection of data sets so large and complex that it becomes difficult to process using on -hand database management tools.Big data can be called as data that’s an order of magni tude greater than data you’re accustomed to.They constitute both structured and unstructured data that grow large so fast that they are not manageable by traditional relational database systems or conventional systems. HADOOP Hadoop was created by DOUNG CUTTING and MICHAEL CA FARELLA in 2005,both worked for Yahoo.Doung had an elephant whose name was HADOOP. Hadoop is an open-source software framework for storing and processing big data in a distributed fashion on large clusters of commodity hardware. Essentially, it accomplishes two tasks: massive data storage and faster process ing.